Opioid-induced constipation in palliative care: state of the art / Constipação induzida por opióides em cuidado paliativo: o estado da arte - Erlania do Carmo Freitas; Geslaney Reis da Silva; Rudval Souza da Silva; Rita Narriman Silva de Oliveira Boery; Maria Patricia Milagres (Universidade Federal do Estado do Rio de Janeiro, 2021)
OBJECTIVE: The study's purpose has been to address the state of the art in investigations such as clinical trials, systematic reviews with meta-analysis and case studies, which report how to minimize opioid-induced constipation in patients undergoing palliative care. METHODS: This is an exploratory study through an integrative review of four databases addressing published articles from 2013 to 2017. RESULTS: A total of 117 publications were presented, which 17 presented the inclusion criteria. The studies describe the prevalence of constipation rates induced by the use of opioids. CONCLUSION: Although these drugs alleviate pain, the adverse reactions may generate discomfort and loss of the patient's life quality. There are limited data on the treatment of constipation. It was observed that few authors mentioned diet as a helper on this situation, emphasizing the use of medications. Further studies should be encouraged aiming to find the balance between analgesia and reduction of adverse effects.